Slouching Towards Decentralization. An Equilibrium Approach for Collective Bargaining. - Gabriele Cardullo (Institute of Labor Economics (IZA), 2024)
Although European institutions and national governments have long pushed for a more decentralized wage bargaining structure, in some countries company or establishment-level negotiations struggle to take place. This paper offers an interpretation for that based on workers' optimal choices in an strategic framework. I construct an equilibrium matching model that explains under which conditions it is best for workers to negotiate their entire wage at sectoral level (one-tier bargaining) or to let a fraction of their salary to be negotiated at company level (two-tier bargaining). Workers' strategies do not simply depend on their own characteristics or on those of their firm, but also on the decisions of all the other employees of the sector. Three alternative Nash equilibria may occur: one-tier bargaining for all workers; two-tier bargaining for all workers; two-tier bargaining for the most productive workers and one-tier bargaining for the others. The prevalence of a specific equilibrium over others hinges on some critical factors, notably the elasticity of the matching function and the properties of the productivity distribution.
Keywords: J50; J52; J31; J64; 330; bargaining structure; wage decentralization; collective bargaining; unions